OX40/OX40L: a new target for tumor immunotherapy and its clinical research progress - Yuan, Zixuan; Pan, Yutong; Yuan, Haodong; Gong, Aihua (Frontiers in Oncology, 2026)
TNFRSF4 (OX40) -TNFSF4 (OX40L) axis is the core costimulatory pathway in the TNF/TNFR superfamily that regulates T cell responses. The binding of OX40L to OX40 on the surface of activated T cells significantly enhanced the proliferation and survival of CD4+ and CD8+ T cells and the secretion of IFN-γ and IL-2, while inhibiting the immunosuppressive activity of regulatory T cells, thereby amplifying the anti-tumor immunity. However, although OX40 agonist monotherapy is well tolerated in phase I/II clinical trials, the objective response rate is lower than that of PD-1 monotherapy, and it does not significantly prolong progression-free survival. At the mechanistic level, insufficient affinity, limited infiltration of T cells in the tumor and residual regulatory T cells are considered to be the main bottlenecks. Despite higher objective response rates with the addition of PD-1, radiotherapy, or chemotherapy, grade 3–4 immune-related adverse events were associated with higher rates. In the future, novel OX40 agonists with high affinity and selective activation in the tumor microenvironment should be developed or incorporated into the framework of combined immunotherapy as an adjuvant strategy to achieve a balance between efficacy and safety.